Effect of violating the contract of monopoly performance artist - Ali Kadhim Jawad, Muthana Mohammed Abid, (Opción, 2019)
The aim of the study is to investigate effect of violating the contract of monopoly performance artist via comparative qualitative research method in light of the previous research problem. As a result, the attack on the moral right is a crime itself and does not require an attack on the financial right to criminalize him. In conclusion, we should highlight some of the financial rights of performers' rights to public performance, namely the public performance of the artist's right to obtain financial rights because of the repeated public broadcasting of television channels